Therapist Attachment and the Working Alliance: The Moderating Effect of Emotional Regulation - Ruiz-Aranda, Desireé; Cardoso-Álvarez, Sara; Fenollar-Cortés, Javier (Frontiers in Psychology, 2021)
Objective: To explore whether the therapist’s emotional regulation strategies moderate the relationship between therapist attachment and the working alliance from the therapist’s perspective. Method: A non‐experimental, descriptive correlational design was used. Sixty-three psychotherapists (6 men, 57 women) participated in this study, ranging in age from 27 to 69 years, with a mean age of 39.3 years. The therapists completed the Attachment evaluation questionnaire for adults, the Spanish Adaptation of the Working Alliance Inventory, and the Difficulties in Emotion Regulation Scale. Associations between attachment and emotional regulation traits and working alliance were examined using multilevel modelling, controlling for therapist demographics and clinical experience. Results: Moderation analyses revealed significant interaction effects between therapist attachment and emotional regulation strategies. Conclusion: Attachment styles would not significantly affect the therapist’s ability to establish an adequate therapeutic alliance bond. The results show that the attachment style of the therapists interacted with their emotional regulation abilities.